Epidemiological evaluation and outcome of pure abdominal trauma victims who underwent surgical exploratory laparotomy - Abd-El-Aal A Saleem; Osama A Abdul Raheem; Hassan A Abdallah; A Mohamed Yousef (Al-Azhar Assiut Medical Journal, 2016)
Objective The aim of this study was to evaluate the epidemiological profile, surgical treatment, and outcome of patients suffering from pure abdominal injuries who underwent exploratory laparotomy in the emergency department of Aswan University Hospital, Egypt. Patients and methods This was an evaluation and assessment of observational and descriptive study with prospective approach through interviews of 80 patients with pure abdominal trauma who were subjected to surgical treatment in the form of exploratory laparotomy and evaluation of their medical records. Results The most affected individuals were male patients younger than 49 years, most of them with low educational level and single. There was a predominance of trauma in the rural areas that mostly occurred at night-time and evening. Blunt trauma was the most common type of abdominal trauma, and road traffic accidents were the most frequent mechanism of trauma. The upper abdomen was the most affected region. Pain was the most common presenting symptom, and the spleen was the most affected organ. The hospital stay ranged from 1 to 11 days. Most patients were discharged with permanent sequelae; there were six deaths. Conclusion Blunt trauma was the most common type of abdominal injury. Road traffic accidents were the most common mechanism of blunt trauma, and stab wounds were the most common type of penetrating injuries. A number of risk factors were identified in this study, which include the type of abdominal trauma, presence of chronic diseases, delay in early transport from the site of trauma to the emergency department, and age of patient. Despite the magnitude of traumas, the outcome was satisfactory.